Faktor Yang Berhubungan Dengan Kejadian Hipertensi Pada Akseptor Pil KB Di Kelurahan Sumbersari Kabupaten Jember Tahun 2014 (The Associated Factors of Hypertension Occurence in Oral Contraceptives User at Sumbersari District Area in Jember Regency) - Dewi Nafisah; Pudjo Wahjudi; Andrei Ramani (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The hypertension is the main factor of cardiovascular disease in the world. The hypertension has various factors, one of the risk factors is oral contraceptives use in woman. Prevalence of hypertension have increased 30,73% in 2012 at Jember with a high prevalence at Sumbersari by 1519 woman with hypertension. The purpose of this study is to analyze the association between age, the duration of using oral contraceptives, type of oral contraceptives and regularity blood pressure checkup with hypertension among oral contraceptives user at Sumbersari District Area in Jember Regency in 2014. This research was cross sectional study.The sample was 70 women who use oral contraceptives in last two years. The result is presented in the table, text and analyzed by Chi-Square with the level significance 5% (á=0,05). The result showed that the average respondent with hypertension is an age 37 years old with the duration of using oral contraceptives 8 year. The most type of oral contraceptives which is used contain 0.03-0.05 mg estrogens and most of them is not regularity blood pressure checkup. There are significant associated between age and the duration of using oral contraceptives with hypertension. However, there are not significant associated between type of oral contraceptives and regularity blood pressure checkup with hypertension. Keyword: Oral Contraceptive User, Hypertension